Disseminated Adenovirus Infection After Combined Liver-Kidney Transplantation - Hemmersbach-Miller, Marion; Bailey, Emily S.; Kappus, Matthew; Prasad, Vinod K.; Gray, Gregory C.; Alspaugh, J. Andrew (Frontiers in Cellular and Infection Microbiology, 2018)
Human adenovirus (HAdV) infections are well-described after hematopoietic stem cell transplantation but less well understood in solid organ transplantation (SOT). We describe a case of disseminated HAdV type 21 infection 5 months after combined liver-kidney transplantation, expanding the limited literature describing this infection in the SOT population.